Achieving the goals - an analysis of irregular migrants' possibilities to transform their space-times in Finland - Gadd Katri (Taylor & Francis (Commercial Publisher), 2022)
This article demonstrates the usefulness of time-geographic approach in research with irregular migrants. Time-geographic approach acknowledges individual space-times as being assembled of multiple elements (e.g. housing, the Internet, friend, fear, legal status). Through an ethnographic research with 50 irregular migrants in Finland, I demonstrate how these irregular migrants try to transform their space-times in order to overcome the adversities in their lives. To transform one's space-times, it is necessary to intervene on the elements that affect it. Irregular migrants in this research transform their space-times, by trying to withdraw from constraining elements (e.g. unpleasant places, dangerous people, fears) and approaching inciting elements (e.g. safe place, friend, knowledge). In this article, I suggest this theoretical-methodological framework to investigate the interlinkages of these multiple elements in the lives of irregular migrants.